2019
DOI: 10.1021/acs.jpclett.9b01789
|View full text |Cite
|
Sign up to set email alerts
|

Titrating Pt Surface with CO Molecules

Abstract: Identification and quantification of the surface sites on Pt nanoparticles are essential for developing more active electrocatalysts for many practical devices such as fuel cells and electrochemical fuel generators. In this work, we studied CO adsorption from dissolved CO in an H 2 SO 4 electrolyte solution on a polycrystalline Pt film electrode held at a constant potential in the underpotential hydrogen deposition region using in situ attenuated total reflectance-surface-enhanced IR absorption spectroscopy (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 67 publications
1
3
0
Order By: Relevance
“…Employing stepped surfaces of the Pt(s)-[(n − 1)(111) × (110)] series, it was shown that the catalytic activity for the CO electro-oxidation reaction increased as the (111) planes became rich in defects. 18,21 On one hand, as shown by the data in Figure 2 (blue line), for a layer of CO ads formed at 0.100 V, the catalytic activities of the Pt surfaces were in the following order (similar to previous results 9 ): Pt(332) > Pt(13 13 12) > Pt(20 20 19) > Pt(111) nondefected . Hence, an evident correlation was established between the surface structure and the catalytic activity for the CO electro-oxidation reaction.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Employing stepped surfaces of the Pt(s)-[(n − 1)(111) × (110)] series, it was shown that the catalytic activity for the CO electro-oxidation reaction increased as the (111) planes became rich in defects. 18,21 On one hand, as shown by the data in Figure 2 (blue line), for a layer of CO ads formed at 0.100 V, the catalytic activities of the Pt surfaces were in the following order (similar to previous results 9 ): Pt(332) > Pt(13 13 12) > Pt(20 20 19) > Pt(111) nondefected . Hence, an evident correlation was established between the surface structure and the catalytic activity for the CO electro-oxidation reaction.…”
Section: Discussionsupporting
confidence: 85%
“…The condition of surface CO saturation implies that all types of Pt sites become occupied by CO ads , including the top sites of the steps, their corresponding bottom sites, and terraces. For the process of CO ads layer formation on a polycrystalline Pt surface in an acid medium, experiments employing slow mass transport (CO extremely diluted or titrating Pt surface with CO molecules 18 ), with monitoring of the CO stretching frequencies of CO ads by in situ attenuated total reflectance surface-enhanced IR absorption spectroscopy, showed that CO preferentially occupies sites consisting of low-coordinated atoms (defects). 18 A similar conclusion was reached previously by Cuesta et al, 19 employing similar spectroscopic techniques.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electrochemical behavior of the Pt/CO system has received a great deal of attention during the last five decades by numerous researchers worldwide. The adsorption and oxidation reaction of CO serves as a testing reaction in surface electrochemistry, with many insights in the field of electrocatalysis, especially those concerning the assignment of active sites, having been obtained by employing the Pt/CO system as a model. However, the vast majority of studies of the adsorption and oxidation of CO on model stepped Pt surfaces have been conducted using acid media. In particular, the application of spectro-electrochemical techniques to study the Pt/CO system using stepped Pt single crystals in alkaline media has received little attention.…”
Section: Introductionmentioning
confidence: 99%